(untitled) (Scientific journal of the Fergana State University, 2024)
The article constantly increases the demand for land resources at the international and local level, the impossibility of acquiring new lands in order to meet the needs of the population and sectors of the national economy for land resources, as well as the process of more intensive use of land resources. The acquired land is increasing, issues are being studied. Changes in the natural and landscape composition of the land fund, along with a decrease in biological diversity, also reduce the land supply of the population, and land resources, which are the main indicator of settlements, affect its territorial organization. Examples explain that this is one of the main factors. Also, given the interdependence of the fields of landscape science and land management, it is argued that it is important to determine land uses as much as possible based on natural and landscape requirements, and to use the principles of landscape planning.